2018
DOI: 10.1021/acs.energyfuels.8b03151
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Effects of Supercritical CO2 Sequestration in Deep Coal Seam

Abstract: CO2 sequestration in deep unminable coal seams is currently identified as a research hot spot to reduce CO2 emissions, due to the potential large-scale storage capacity and complicated physical and chemical reactions, especially for supercritical CO2 (scCO2). Hitherto, the interaction mechanisms between scCO2 and coal mass in situ conditions are still unclear. Therefore, the main objective of this study is to fully address the coupling effects of scCO2 sequestration on coal mass and provide a comprehensive eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 79 publications
1
10
0
Order By: Relevance
“…The aliphatic hydrocarbon chain length (L = A 2925 /A 2950 ) showed irregular changes. Zhang et al found that aliphatic hydrocarbons in coal are more easily extracted by Sc-CO 2 than aromatic hydrocarbons [54]. Because of the low content of aliphatic hydrocarbons in the shale, the aliphatic hydrocarbons peaks in the FTIR spectrum were, at best, subtle and the peak fitting results obtained were not very good.…”
Section: (A) Changes In Hydroxyl Structuresmentioning
confidence: 99%
“…The aliphatic hydrocarbon chain length (L = A 2925 /A 2950 ) showed irregular changes. Zhang et al found that aliphatic hydrocarbons in coal are more easily extracted by Sc-CO 2 than aromatic hydrocarbons [54]. Because of the low content of aliphatic hydrocarbons in the shale, the aliphatic hydrocarbons peaks in the FTIR spectrum were, at best, subtle and the peak fitting results obtained were not very good.…”
Section: (A) Changes In Hydroxyl Structuresmentioning
confidence: 99%
“…the swelling ratio of the coal matrix decreases with increasing R o,max (Majewska et al., 2010; Yu et al., 2003). Furthermore, the extraction effect and mineral dissolution and precipitation effects have been found to depend upon the volatile matter yield and ash content, respectively (Zhang et al., 2013a, 2019a). Based on this, the changing amplitude of the micropore surface area (| f S mic |) and micropore volume (| f V mic |) were plotted against R o,max .…”
Section: Effects Of Scco2 On the Pore Morphology Of Coalsmentioning
confidence: 99%
“…Jiang et al [50] found that crystal water was released from clay minerals after ScCO 2 treatment. Previous studies have shown that some carbonate minerals are dissolved and some hydrocarbons are extracted and washed away by the gas or water after ScCO 2 treatment [23,26]. The chemical reactions are listed in Equations (4) and (5).…”
Section: Ir Indexmentioning
confidence: 99%
“…These continuous pores are conducive to CH 4 desorption and flow. Therefore, CO 2 could enhance coalbed methane recovery and can be stored in the coal seam [26].…”
Section: Ir Indexmentioning
confidence: 99%
See 1 more Smart Citation